HOMOGENEITY WITHIN LAYLÁ BA‘ALBAKĪ’S SHORT STORIES - Igbaria, Khaled (PEOPLE: International Journal of Social Sciences, 2018)
This article discusses selectively Laylá Ba‘albakī’s short stories–the twelve collected in Safīnat ḥanān ilá al-qamar [A spaceship of tenderness to the moon] (2009), as well as al-Batal [The hero] (1966). This discussion aims to explore the feminist writing of the writer, arguing the existence of homogeneity, which the interweaving and interconnections create among those short stories. This literary analysis begins with an examination of narrative manner, including the narrator, style, and language used, and then turns to the major themes, which run through the stories (Igbaria, 2015).Since the short stories that were as the rationale for bringing the author to trial, a particular aim in what follows is to provide the necessary literary analysis to evaluate the court’s charges of obscenity. As we will see, Ba‘albakī’s defence was that she was simply describing real life as experienced by women. This paper provides the groundwork for any later discussion of this issue.